2000
DOI: 10.1128/aem.66.9.3674-3679.2000
|View full text |Cite
|
Sign up to set email alerts
|

Response of Atmospheric Methane Consumption by Maine Forest Soils to Exogenous Aluminum Salts

Abstract: Atmospheric methane consumption by Maine forest soils was inhibited by additions of environmentally relevant levels of aluminum. Aluminum chloride was more inhibitory than nitrate or sulfate salts, but its effect was comparable to that of a chelated form of aluminum. Inhibition could be explained in part by the lower soil pH values which resulted from aluminum addition. However, significantly greater inhibition by aluminum than by mineral acids at equivalent soil pH values indicated that inhibition also result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…1c). The results indicated that low Al concentrations in the upper soil layers supported a larger consumption of CH 4 and C 2 H 4 in forest surface soils, due to Al toxic effect on methanotrophs ( Nanba and King, 2000;Tamai et al, 2003Tamai et al, , 2007. More interestingly, it was observed that maximum Al concentrations occurred in subsurface soil rather than in surface soil layers under spruce and birch (P ≤ 0.05) (Table 1), which paralleled the maxima of the CH 4 and C 2 H 4 consumption activity in forest soils at various depths (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…1c). The results indicated that low Al concentrations in the upper soil layers supported a larger consumption of CH 4 and C 2 H 4 in forest surface soils, due to Al toxic effect on methanotrophs ( Nanba and King, 2000;Tamai et al, 2003Tamai et al, , 2007. More interestingly, it was observed that maximum Al concentrations occurred in subsurface soil rather than in surface soil layers under spruce and birch (P ≤ 0.05) (Table 1), which paralleled the maxima of the CH 4 and C 2 H 4 consumption activity in forest soils at various depths (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Although not intended to be synoptic, results from pmoA analyses are consistent with other studies 14,27,33,39) that reveal a limited number of taxa, often including novel lineages. Notably, the extent of diversity for facultative lithotrophs and CO-oxidizing bacteria in Hawaiian volcanic deposits appears much greater than that for methanotrophs 11,31) . Again, this suggests a limited role for methanotrophs in developing Hawaiian ecosystems.…”
Section: Molecular Ecological Analysesmentioning
confidence: 99%
“…Despite the general agreement that Al toxicity derives from its replacement of divalent metal complexes, chiefly Mg and Ca, in cells or cell membranes, there is less agreement about whether the effect is generic to all forms of soluble Al. Stable organic complexes of Al (e.g., oxalate or citrate) seem to mitigate the toxic effects on methanotroph activity (25) and root growth (13). However, citrate complexes also seem to be the mechanism by which soluble Al crosses the blood-brain barrier (46).…”
mentioning
confidence: 99%